KEBUTUHAN PENELITIAN UNTUK PENINGKATAN PROGRAM PELAYANAN KESEHATAN REPRODUKSI - Firman Lubis (Populasi, 1994)
One important matter to be faced in improving the reproductive health is how to increase the coverage of KIA-KB services (Mother-and-Child Health Family Planning services) at the Puskesmas (Community Health Center) level. The Puskesmas also has the position of a reproductive health reference for the fieldworkers and facilities underneath it such as the traditional midwives. the Posyandu (Integrated Health Service Post), and the village midwives This article puts special stress on the fact that the improvement of coverage and quality of reproductive health services have become substantially important due to the still high matemal-and-infant mortality rate, maternal-and-infant morbidity rate, and the fertility rate. Besides, the knowledge, attitudes, and behaviour of the community towards reproductive health is still considered very limited. For this reason, a morespecific study is advisable to be carried out to be able to provide certain inputs on how to increase the coverage as well as quality of KIA-KB services through the existing health facilities